2019
DOI: 10.1111/jsr.12928
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and gender minority sleep: A narrative review and suggestions for future research

Abstract: SummaryThis article reviews a growing body of research that examines sleep among lesbian, gay, bisexual and transgender (LGBT) populations. An extensive search of the literature was conducted using multiple medical and psychological search engine platforms. In total, this search yielded 31 reports that included sleep data collected from sexual and gender minority participants. Overall, research findings are mixed and include several publications of studies conducted in the same sample. Our review suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 80 publications
1
64
1
Order By: Relevance
“…This finding suggests that variation in hormone levels—including between individuals with the same chromosomal sex—could influence mitochondrial behavior regardless of sex assigned at birth. Moreover, independent of biological sex, gender (e.g., identifying as a woman, man, or another identity; being more traditionally masculine or feminine) influences diet, 60–62 physical activity, 63–66 sleep, 67–69 and other health behaviors 70–72 . In turn, these factors can drive physiological differences in mitochondrial biology.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that variation in hormone levels—including between individuals with the same chromosomal sex—could influence mitochondrial behavior regardless of sex assigned at birth. Moreover, independent of biological sex, gender (e.g., identifying as a woman, man, or another identity; being more traditionally masculine or feminine) influences diet, 60–62 physical activity, 63–66 sleep, 67–69 and other health behaviors 70–72 . In turn, these factors can drive physiological differences in mitochondrial biology.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have important implications for future research on multimorbidity in sexual minority adults across the life course. Despite higher rates of risk factors for chronic diseases including tobacco use (Blosnich et al, 2013), heavy drinking (Caceres, Makarem, et al, 2019; Dermody et al, 2014), and sleep disturbances (Butler et al, 2020; Caceres, Hickey, et al, 2019), the study of multimorbidity among sexual minority adults is limited. Even fewer studies have examined the experiences of sexual minority adults with multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The minority stress model postulates that exposure to unique minority stressors (e.g., sexual orientation–based discrimination, bias-motivated violence, and expectations of rejection) contributes to negative health outcomes among sexual minority individuals. A growing body of research indicates that sexual minority adults have a higher prevalence of current tobacco use (Blosnich et al, 2013), heavy drinking (Caceres, Makarem, et al, 2019; Dermody et al, 2014), and short sleep duration (Butler et al, 2020; Caceres, Hickey, et al, 2019) relative to heterosexual adults. In addition, sexual minority adults report higher rates of mental health conditions (e.g., depression, anxiety, and suicidal ideation) (Plöderl & Tremblay, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review on sleep among gender minority participants, only 4 of 31 studies included transgender subjects. 34 Poor sleep quality is prevalent in non-college transgender women (79.2%) and transgender men (81.2%). 13 A qualitative study of transgender adults, of which 25% were between the ages of 18-21 years-old, observed high proportions of poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%